2021
DOI: 10.1111/geoj.12413
|View full text |Cite
|
Sign up to set email alerts
|

Reframing resilience as resistance: Situating disaster recovery within colonialism

Abstract: Much of the resilience literature myopically focuses on actors' responses to exogenous hazards, implicitly suggesting that resilient actors are merely adapting, mitigating, or recovering from a hazard (Chandler, 2012). This strips actors of their political agency and reduces actions to no more than survival and coping (Bohle et al., 2009). However, recent scholarship has explored the political potential of resilient actors by focusing on the connection between resilience and resistance (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The main goal of resilience is to reduce the effects of a disturbance, a concept that exists in different research areas with very similar de nitions [57][58][59]. However, there is no uniform and applicable de nition in different elds, which includes several features such as self-organization [60, 60, 61], speed [62,63], recovery [64-67], preservation and survival [53,68], balance [69,70], and resistance [32,71,72]. Therefore, it can be concluded that resilience is the ability of societies to react and recover from disasters and includes those inherent conditions that allow the system to absorb the effects and deal with an event [73,74].…”
Section: Resiliencementioning
confidence: 99%
“…The main goal of resilience is to reduce the effects of a disturbance, a concept that exists in different research areas with very similar de nitions [57][58][59]. However, there is no uniform and applicable de nition in different elds, which includes several features such as self-organization [60, 60, 61], speed [62,63], recovery [64-67], preservation and survival [53,68], balance [69,70], and resistance [32,71,72]. Therefore, it can be concluded that resilience is the ability of societies to react and recover from disasters and includes those inherent conditions that allow the system to absorb the effects and deal with an event [73,74].…”
Section: Resiliencementioning
confidence: 99%
“…A subject of significant academic attention and debate, resilience is perhaps one of the most contested concepts in disaster scholarship (as well as in other disciplines!) (Rogers 2015;Humbert and Joseph 2019;Chandler 2020;Joseph 2021;Sou 2021;Wakefield et al 2021). We will not rehearse the evolution of the concept as this has been sufficiently covered in the literature (for example , Mayena 2006;Alexander 2013;Gaillard and Jigyasu 2016); but in the context of disasters, in a normative sense, we maintain resilience is both a desired outcome and a process leading to a desired outcome, with the definitions largely focussing on ideas of the ability to self-organize and the capacity to learn, to change, and to adapt, its understandings remaining nebulous and malleable.…”
Section: Resilient Citiesmentioning
confidence: 99%
“…These responses reflect a broader concern that early response to Covid-19 was underpinned by a tension between formal and informal efforts whilst asserting scepticism concerning the capacity of informal efforts to remain efficacious in the long term (See also Sou, 2021 ). However, and owing to the pandemic’s potential to overwhelm those resources governments’ had at the existing disposal, these informal practices proved essential to developing adequate response to the pandemic.…”
Section: Findings: People In a Pandemicmentioning
confidence: 99%